Floral aroma improvement of Muscat spirits by packed column distillation with variable internal reflux. (15th December 2016) - Matias-Guiu, Pau; Rodríguez-Bencomo, Juan José; Orriols, Ignacio; Pérez-Correa, José Ricardo; López, Francisco
Highlights: Variable reflux packed column to concentrate terpenic compounds in spirits. Comparison between variable reflux packed column and alembic distillations. Reduction of column reflux in heart distillation enhanced floral aromas. Abstract: The organoleptic quality of wine distillates depends on raw materials and the distillation process. Previous work has shown that rectification columns in batch distillation with fixed reflux rate are useful to obtain distillates or distillate fractions with enhanced organoleptic characteristics. This study explores variable reflux rate operating strategies to increase the levels of terpenic compounds in specific distillate fractions to emphasize its floral aroma. Based on chemical and sensory analyses, two distillate heart sub-fractions obtained with the best operating strategy found, were compared with a distillate obtained in a traditional alembic. Results have shown that a drastic reduction of the reflux rate at an early stage of the heart cut produced a distillate heart sub-fraction with a higher concentration of terpenic compounds and lower levels of negative aroma compounds. Therefore, this sub-fraction presented a much more noticeable floral aroma than the distillate obtained with a traditional alembic.